Efficient Multiscale Template Matching with Orthogonal Wavelet Decompositions - Basu, Sumit (Perceptual Computing Section, The MIT Media Laboratory, 1997)
I develop a method for efficient, multiscale template matching using orthogonal wavelet representations. I also develop an efficient approximate mechanism for initially finding the " values for the basis coefficients ajk at the finest scale (as opposed to using the sample values as coefficients). I then present applications of these techniques to two important image coding/computer vision tasks: motion estimation and multiple model matching (model recognition).
Massachusetts Institute of Technology Technical Report. May, 1007.